Multiple and solitary skeletal muscle metastases on 18F-FDG PET/CT imaging. Issue 11 (November 2015) - Nocuń, Anna; Chrapko, Beata
Abstract : Objective: The aim of this study was to investigate the features and patterns of skeletal muscle metastases (SMM) detected with 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (PET/CT). Participants and methods: Our database was analyzed for patients with pathologically proven malignancy, who underwent 18 F-FDG PET/CT in our institution. The patients with SMM were included in the study group on the basis of the final diagnosis confirmed by follow-up or histopathology. Images were acquired using a PET/CT system Biograph mCT S(64)-4R. CT was performed without contrast enhancement. Results: The selected group included 31 patients (1.7% of the database, which consisted of 1805 patients). A total of 233 lesions were found. The prevalence of SMM evaluated in specific primary malignancies was the highest in melanoma (6.9%), followed by carcinoma of unknown primary (4.4%), colorectal cancer (4.1%) and lung cancer (2.8%). Three patterns of skeletal muscle metastatic involvement were observed: multiple SMM accompanied by other metastases (64.5%), solitary lesion associated with other metastases (29%) and isolated intramuscular lesions (two cases, 6.5%). Isolated SMM represented recurrence of the malignant disease. In patients with extraskeletal metastases, solitary or multiple SMM did not affect tumor staging. Conclusion: Solitary SMM are less common than multiple on 18 F-FDG PET/CT imaging. SMM are usually associated with other metastases and do not affect tumor staging. The cases of isolated SMM are very rare. Nevertheless, in patients with a diagnosis of malignant disease, a solitary, 18 F-FDG avid intramuscular focus should be suspected to represent metastasis.